Application of “Monte-Carlo” method for estimation of hydrocarbonic reserves - KURHANSKYI, V.; KOLISNICHENKO, V.; MALIAR, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
It is describing the application of the probability functions for determination calculation parameters. Application of "Monte Carlo" method for estimation of hydrocarbonic reserves is shown. Algorithm of calculations and research results are described.